The electrocardiographic diagnosis of apical infarction. Issue 649 (November 1979) - Talbot, Stephen; Kilpatrick, David; Weeks, Barbara
Abstract : Dyskinetic areas of the left ventriculograms of 151 patients were related to electrocardiographic signs of infarction. Apical dyskinesia alone or in combination with anterior or inferior dyskinesia could be associated with inferior and/or anterior infarction patterns. Appreciation of this fact prevents over-estimation of the severity of coronary artery disease from a resting electrocardiogram, showing both 'anterior and inferior infarction'.